Features of correction of disorders of the digestive system in children with reactive asthenic syndrome - A. M. Levchin; I. B. Ershova; A. G. Rogovtsova (Медицинский вестник Юга России, 2024)
Objective: to study the features of the digestive system in children with reactive asthenic syndrome and correction of disorders using a comprehensive integration program.Materials and methods: a prospective cohort non-randomized study of 419 children of primary school age was conducted. The main group consists of 128 children living in the territory of active hostilities. Control group — 291 children outside the zone of active hostilities. A full examination was carried out before and 6 months after the start of the comprehensive integration rehabilitation program. All children were collected complaints, anamnesis, analysis of outpatient records, objective examination, examination of the motor-evacuation function of the gastrointestinal tract.Results: all children of the main group had complaints from the digestive system. 97 (75.78%) children were concerned about decreased appetite; 79 (61.72%) — stool disorders. Functional disorders were registered in 80 (62.50%) children of the main group, organic pathology — in 62 (48.44%). Among functional abnormalities, functional disorders of the biliary tract were in the first place (in 65 (50.78%) people). Among the organic pathology — diseases of the stomach and 12-duodenum (in 59 (46.09%) children). Peripheral electrogastroenterography revealed in most children of the main group non-impulsive contractions and discoordination of motor skills of varying degrees of severity in all parts of the gastrointestinal tract.Conclusions: the implementation of complex rehabilitation measures optimized the studied indicators with more pronounced effectiveness in children evacuated from active combat zones.